Development of an integrated microfluidic device for cell lysis and DNA purification - Elahe Jalilvand; Amir Shamloo (Results in Engineering)
Cell studies are essential for investigating cellular complications. Microfluidic techniques enable the study and control of fluid behavior in microstructures, providing a fast, precise, and efficient tool for cell analysis.Nowadays, various microfluidic devices are integrated into a single platform to conduct multiple investigations within one device, minimizing costs, material waste, response time, and contamination while enhancing efficiency, portability, and automation. Accordingly, this study developed an integrated microfluidic device for cell lysis and DNA purification. Chemical cell lysis was performed on three types of cells: fibroblasts, MCF-7, and WBCs. A serpentine micromixer, combined with internal and external barriers at the microchannel entrance, was used to enhance mixing and improve cell lysis. A sandwich mechanism was implemented in the inlets to create crosswise flow for better mixing. A reservoir was incorporated in the middle of the channel for heating, while an absolute ethanol inlet was designed to ensure complete lysis. At the end of the channel, extracted DNA was captured by a filter, and three types of washing buffers were used for DNA purification. Finally, PCR and DNA electrophoresis were performed on the purified DNA.The mixing efficiency of the system was evaluated using both computational and experimental methods. In the experimental study, two-colored fluids and FITC/water were used separately. The average mixing efficiency at the end of the channel was 98.95 %, differing by only 1.01 % from the computational results. Additionally, the presence of an opaque substance at the channel's end and the results of the live/dead test confirmed the completion of cell lysis. A nanodrop test was conducted to quantify DNA concentration and assess device efficiency, which were measured at 76.437 ng/μL and 97.13 %, respectively. Finally, the observation of clear DNA electrophoresis and PCR bands corresponding to two different primers validated the applicability of the proposed microfluidic platform for clinical analysis.